2020
DOI: 10.1038/s41419-020-03111-7
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting tumor cell-derived CCL2 as a strategy to overcome Bevacizumab resistance in ETV5+ colorectal cancer

Abstract: In our previous study, ETV5 mediated-angiogenesis was demonstrated to be dependent upon the PDGF-BB/PDGFR-β/Src/STAT3/VEGFA pathway in colorectal cancer (CRC). However, the ability of ETV5 to affect the efficacy of anti-angiogenic therapy in CRC requires further investigation. Gene set enrichment analysis (GSEA) and a series of experiments were performed to identify the critical candidate gene involved in Bevacizumab resistance. Furthermore, the ability of treatment targeting the candidate gene to enhance Beva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 48 publications
0
38
0
Order By: Relevance
“…CCL2 production has been reported to be more inducible in HER2+/ER− breast carcinoma cells compared with HER2+/ER+ cells under EGF/HRG stimulation, and enhanced NF-kB transcription levels were detected in HER2+/ER− breast carcinoma cells (5). Emerging evidence indicates that the JAK/STAT pathway can also promote CCL2 production under stimulation (6)(7)(8)(9)(10)(11)(12)(13). Neddylation is a reversible protein modification process mediated by NEDD8.…”
Section: Regulation Of Ccl2 Productionmentioning
confidence: 99%
“…CCL2 production has been reported to be more inducible in HER2+/ER− breast carcinoma cells compared with HER2+/ER+ cells under EGF/HRG stimulation, and enhanced NF-kB transcription levels were detected in HER2+/ER− breast carcinoma cells (5). Emerging evidence indicates that the JAK/STAT pathway can also promote CCL2 production under stimulation (6)(7)(8)(9)(10)(11)(12)(13). Neddylation is a reversible protein modification process mediated by NEDD8.…”
Section: Regulation Of Ccl2 Productionmentioning
confidence: 99%
“…Angiogenesis is an essential process in CRC progression, and the VEGF-VEGF receptor pathway blockade by bevacizumab is a major target in drug therapy [111]. However, in some cases of CRC, E26 transformation-specific mutant 5 of the ETS family is activated, and CCL2 is secreted to promote angiogenesis and acquire resistance to bevacizumab [112]. Type I γ phosphatidylinositol phosphate kinase (PIPKI γ) plays an important role in multiple biological processes and enhances PD-L1 expression in cancer cells to evade anticancer immunity [113].…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Besides, patients with the same tumor stage sometimes had survival differences (Liu et al, 2019). In the last decade, studies have shown that different molecular typing influences the response to treatment and prognosis of HCC, such as the expression status of programmed cell death protein 1 (PD-1), suggesting different sensitivity to immunotherapy (Scheiner et al, 2019;Feng et al, 2020a). New molecular typing studies are expected to provide novel biomarkers with higher specificity and sensitivity for predicting the prognosis of HCC.…”
Section: Discussionmentioning
confidence: 99%